Comparison of the Simulated Response of Three in Silico Human Stem Cell-Derived Cardiomyocytes Models and in Vitro Data Under 15 Drug Actions - Paci, Michelangelo; Koivumäki, Jussi T.; Lu, Hua Rong; Gallacher, David J.; Passini, Elisa; Rodriguez, Blanca (Frontiers in Pharmacology, 2021)
Improvements in human stem cell-derived cardiomyocyte (hSC-CM) technology have promoted their use for drug testing and disease investigations. Several in silico hSC-CM models have been proposed to augment interpretation of experimental findings through simulations. This work aims to assess the response of three hSC-CM in silico models (Koivumäki2018, Kernik2019, and Paci2020) to simulated drug action, and compare simulation results against in vitro data for 15 drugs. First, simulations were conducted considering 15 drugs, using a simple pore-block model and experimental data for 7 ion channels. Similarities and differences were analyzed in the in silico responses of the three models to drugs, in terms of Ca2+ transient duration (CTD) and occurrence of arrhythmic events. Then, the sensitivity of each model to different degrees of blockage of Na+ (INa), L-type Ca2+ (ICaL), and rapid delayed rectifying K+ (IKr) currents was quantified. Finally, we compared the drug-induced effects on CTD against the corresponding in vitro experiments. The observed CTD changes were overall consistent among the in silico models, all three showing changes of smaller magnitudes compared to the ones measured in vitro. For example, sparfloxacin 10 µM induced +42% CTD prolongation in vitro, and +17% (Koivumäki2018), +6% (Kernik2019), and +9% (Paci2020) in silico. Different arrhythmic events were observed following drug application, mainly for drugs affecting IKr. Paci2020 and Kernik2019 showed only repolarization failure, while Koivumäki2018 also displayed early and delayed afterdepolarizations. The spontaneous activity was suppressed by Na+ blockers and by drugs with similar effects on ICaL and IKr in Koivumäki2018 and Paci2020, while only by strong ICaL blockers, e.g. nisoldipine, in Kernik2019. These results were confirmed by the sensitivity analysis. To conclude, The CTD changes observed in silico are qualitatively consistent with our in vitro data, although our simulations show differences in drug responses across the hSC-CM models, which could stem from variability in the experimental data used in their construction.